Currículo e identidades étnico-raciais : desafios na implementação da Lei 10.639/03 no ensino médio da EJA em Alvorada/RS - Rosa, Alan Barcellos da (2017)
This research project aims at discussing the implementation of the federal law 10.639/03 in the EJA (young and adult education) school curriculum, based on the construction of students’ ethnic-racial identities, from the research interlocutors’ perception. The aforementioned law, which made the teaching of African and afro-Brazilian history and culture mandatory in the school curriculum, was passed in 2003 and, despite the time of its creation, its practical application is still little spread. Based on this context, this study aims at understanding the implementation process of the law 10.639/03 in a public school of Alvorada City /RS that offers EJA as a modality in High School. Methodologically, this paper will prioritize the construction of qualitative and quantitative data, combining the use of questionnaires only for the studentes and semi-strucured interviews for teachers, students and directing team of the school.